2020
DOI: 10.5123/s1679-49742020000100025
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de microrregiões com subnotificação de casos de tuberculose no Brasil, 2012 a 2014*

Abstract: Objective: to identify Brazilian micro-regions with under-reported tuberculosis cases, from 2012 to 2014. Methods: this was an ecological study using data from the Notifiable Health Conditions Information System (SINAN). The indirect estimator of the proportion of notified cases (EIPCN) was calculated as the mean between the proportion of cases that adhered to treatment and the proportion of those who underwent sputum smear microscopy. Negative Binomial Regression was used to investigate evidence of under-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
4
1
3
Order By: Relevance
“…In a context of low testing and lack of standardization in data notification, a technical note pointed out rates of underreporting of deaths in Santa Catarina during the COVID-19 pandemic near 278%. 16 The excess deaths found in this study was 27.4% higher than the number of cumulative deaths due to COVID-19 and reported by the state. A possible explanation for this lies in the fact that excess deaths are not an indicator affected by the classification of causes of death, therefore they have not been affected by the high underreporting.…”
Section: Discussioncontrasting
confidence: 55%
“…In a context of low testing and lack of standardization in data notification, a technical note pointed out rates of underreporting of deaths in Santa Catarina during the COVID-19 pandemic near 278%. 16 The excess deaths found in this study was 27.4% higher than the number of cumulative deaths due to COVID-19 and reported by the state. A possible explanation for this lies in the fact that excess deaths are not an indicator affected by the classification of causes of death, therefore they have not been affected by the high underreporting.…”
Section: Discussioncontrasting
confidence: 55%
“…Surveillance is a primary action of public health; 19 ),( 20 however, it is recognized that weak surveillance systems can lead to underreporting of TB. 21 It is possible that this weakness may be accentuated in the context of COVID-19. Studies conducted in India and Sierra Leone showed a reduction of 63.3% and 70.0% in TB notifications, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As this was an ecological study, possible limitations due to the occurrence of bias or confounders cannot be ruled out. The underreporting of deaths stands out as a potential bias, observed in studies that used secondary data [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%